Tunable Dual Broadband Terahertz Metamaterial Absorber Based on Vanadium Dioxide - Xiao-Fei Jiao; Zi-Heng Zhang; Tong Li; Yun Xu; Guo-Feng Song (Applied Sciences, 2020)
With the rapid development of terahertz technology, tunable high-efficiency broadband functional devices have become a research trend. In this research, a dynamically tunable dual broadband terahertz absorber based on the metamaterial structure of vanadium dioxide (VO2) is proposed and analyzed. The metamaterial is composed of patterned VO2 on the top layer, gold on the bottom layer and silicon dioxide (SiO2) as the middle dielectric layer. Simulation results show that two bandwidths of 90% absorption reach as wide as 2.32 THz from 1.87 to 4.19 THz and 2.03 THz from 8.70 to 10.73 THz under normal incidence. By changing the conductivity of VO2, the absorptance dynamically tuned from 2% to 94%. Moreover, it is verified that absorptance is insensitive to the polarization angle. The physical origin of this absorber is revealed through interference theory and matching impedance theory. We further investigate the physical mechanism of dual broadband absorption through electric field analysis. This design has potential applications in imaging, modulation and stealth technology.